2014
DOI: 10.4103/2141-9248.126608
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology in pediatric age group with special reference to pediatric tumors: A retrospective study evaluating its diagnostic role and efficacy

Abstract: Background:Fine needle aspiration cytology (FNAC) is a well-established diagnostic technique in adult mass lesions but a comparatively new technique to pediatric lesions.Aim:The current study aims to evaluate the role of FNAC in pediatric age with special reference to pediatric tumors.Subjects and Methods:A retrospective study of FNAC in children ≤ 18 years of age presenting with mass lesions was studied for 5 years. Distribution of cases in different age groups, sex, and site of lesion was analyzed. Pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…4 Fortunately benign masses are more frequently encountered which are reaction to the upper airway infection. [5][6][7] Problems related to precise diagnosis and proper management of a child with head and neck mass is challenging for both the surgeon and the pathologist. Lesions found in these regions can be indicative of more extensive disorder such as haemopoitic malignancy or can be a manifestations of a locally invasive and destructive process.…”
Section: Introductionmentioning
confidence: 99%
“…4 Fortunately benign masses are more frequently encountered which are reaction to the upper airway infection. [5][6][7] Problems related to precise diagnosis and proper management of a child with head and neck mass is challenging for both the surgeon and the pathologist. Lesions found in these regions can be indicative of more extensive disorder such as haemopoitic malignancy or can be a manifestations of a locally invasive and destructive process.…”
Section: Introductionmentioning
confidence: 99%
“…16 Prathima et al, 13 showed concordant results in 81.6% cases with cyto-histopathological correlation in 9.4% cases.…”
mentioning
confidence: 85%
“…13 study showed cervical lymph node as the commonest site for FNAC accounting for 48.3%. Reactive lymphadenitis followed by acute suppurative lesion was the most common lesions among nonneoplastic lesions, accounting for 38.8% and 16.22% respectively.…”
mentioning
confidence: 98%
“…This has also been found to have contributed into its increasing popularity and utilization in preoperative diagnosis. However, there are few reports on head and neck FNAC in the published studies in Nigeria [3,8,9]. This study aims to highlight the relevance of FNAC and to draw attention to its prospects and challenges in the management of head and neck masses.…”
Section: Introductionmentioning
confidence: 99%